Comparison of the application of the attenuated Salmonella Enteritidis or Salmonella Typhimurium vaccines by different routes in chicks - Joaquim, Patricia Estefania; Balbiani, Facundo; Rodriguez, Andrea; Socas, Maria Laura; Quispe Chosgo, Tamara Belen; Sisquella, Lourdes; Gomez, Maria; Chacana, Pablo (Asociación Española de Ciencia Avícola, 2026)
Poster